2020
DOI: 10.1111/jch.13876
|View full text |Cite
|
Sign up to set email alerts
|

Masked and white coat hypertension, the double trouble of large arteries: A systematic review and meta‐analysis

Abstract: Registration number (DOI): Available in https://osf.io/974gb/, https://doi.Abstract Arterial damage of large arteries, addressed as c-f PWV, is recognized as independent predictor for future cardiovascular disease. The aim of this study was to systematically investigate the association of the four hypertension phenotypes with carotidfemoral pulse wave velocity (c-f PWV), in untreated patients. PubMed and Cochrane Library were searched to identify studies comparing c-f PWV levels between normotensives, sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…Based on previous [26,27] and current observations, we conclude that chronic foot shock stress induces elevated AQP1 expression in the kidneys via the renal sympathetic nerve system, renin-angiotensin system, and oxidative stress by regulation of vasopressin level. These findings have been schematized in Figure 6.…”
Section: Discussionsupporting
confidence: 70%
“…Based on previous [26,27] and current observations, we conclude that chronic foot shock stress induces elevated AQP1 expression in the kidneys via the renal sympathetic nerve system, renin-angiotensin system, and oxidative stress by regulation of vasopressin level. These findings have been schematized in Figure 6.…”
Section: Discussionsupporting
confidence: 70%
“…A meta‐analysis in this issue of the Journal of Clinical Hypertension adds to the current knowledge by evaluating pulse wave velocity (PWV), an index of arterial stiffness, in WCH and MH in comparison with normotension and sustained hypertension 7 . Seven studies including 2352 subjects were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…However, their prognostic significance has to be demonstrated beyond the established risk factors such as blood pressure (BP), cholesterol levels, diabetes mellitus, smoking, as well as age and sex 3 . It has been shown that increased arterial stiffness may predict cardiovascular events in asymptomatic individuals with 4 or without overt CV disease 5 . As such, arterial stiffness has been recommended as a useful prognostic biomarker 6 .…”
Section: The Application Of Arterial Stiffness Measurements In Clinicmentioning
confidence: 99%